Evaluation of the efficiency of the hepatoprotector glucuronate in toxic hepatitis of various etiology - R. N. Akalaev; A. M. Khadjibaev; A. A. Stopnitskiy; D. B. Tulyaganov; U. R. Kamilov; M. K. Saidova (Вестник анестезиологии и реаниматологии)
The objective was to study the effectiveness of the use of hepatoprotector glucuronate at the early stage of intensive therapy of toxic hepatitis of various etiologies.Materials and methods. We studied 120 patients with toxic hepatitis who were treated at the Republican research center for emergency medicine in 2022–2023. The study was carried out in two groups of patients. Group I – 60 patients admitted in 2023, who, in addition to traditional therapy, received a complex hepatoprotector glucuronate (Jetepar®)*. Group II (comparison group) – 60 patients who applied in 2022 and received only traditional therapy. Biochemical blood parameters were studied upon admission and over time on day 5. The severity of intellectual impairment was assessed using cognitive scales and the Reitan test on days 2 and 5 from the start of treatment.Results. Upon admission, both groups showed signs of toxic liver damage. In dynamics by the 5th day in patients of group I, there was a decrease in ALT by 63.7%, AST by 66.4%, alkaline phosphatase by 54.2% from the initial values, which was 3.9 and 2.6, 2. 1 lower than in the comparison group. The level of free ammonia in patients of group I on the 5th day decreased by 52%, and lactate by 57% from the initial level, almost to the physiological norm, while in the comparison group (II) only by 24.8% and 38.1%, which was 2.2 and 1.5 times worse than in the main group. Screening of the level of intelligence using two cognitive scales and the Reitan test showed that in patients in the comparison group, cognitive function indicators on the 5th day were 1.4, 1.5 and 1.2 times lower than in the main group.Conclusion. The use of the hepatoprotector glucuronate improves liver parameters and cognitive functions in patients with toxic hepatitis.